The in-laws [videorecording (DVD)] - Gerber, Bill; Samaha, Elie, 1955-; Todman, Bill, Jr; Simon, Joel, 1950-2011; Mauldin, Nat; Solomon, Ed; Fleming, Andrew, 1963-; Douglas, Michael, 1944-; Brooks, Albert, 1947-; Tunney, Robin; Reynolds, Ryan; Suchet, David; et al. (Warner Home Video, 2003)
When two fathers of an engaged couple meet for the first time, they know they are very different. One is a podiatrist, happy with his quiet life. The other is a CIA operative, who lives life on the edge, and when circumstances get out-of-hand, involves the other in an arms-smuggling sting.